Designing Next‐Generation Local Drug Delivery Vehicles for Glioblastoma Adjuvant Chemotherapy: Lessons from the Clinic. Issue 3 (11th January 2019) - Tabet, Anthony; Jensen, Melanie P.; Parkins, Christopher C.; Patil, Parag G.; Watts, Colin; Scherman, Oren A.
Abstract: To date, the clinical outcomes and survival rates for patients with glioblastoma (GB) remain poor. A promising approach to disease‐modification involves local delivery of adjuvant chemotherapy into the resection cavity, thus circumventing the restrictions imposed by the blood–brain barrier. The clinical performance of the only FDA‐approved local therapy for GB [carmustine (BCNU)‐loaded polyanhydride wafers], however, has been disappointing. There is an unmet medical need in the local treatment of GB for drug delivery vehicles that provide sustained local release of small molecules and combination drugs over several months. Herein, key quantitative lessons from the use of local and systemic adjuvant chemotherapy for GB in the clinic are outlined, and it is discussed how these can inform the development of next‐generation therapies. Several recent approaches are highlighted, and it is proposed that long‐lasting soft materials can capture the value of stiff BCNU‐loaded wafers while addressing a number of unmet medical needs. Finally, it is suggested that improved communication between materials scientists, biomedical scientists, and clinicians may facilitate translation of these materials into the clinic and ultimately lead to improved clinical outcomes. Abstract : There is an unmet medical need in glioblastoma adjuvant chemotherapy for drug delivery carriers that provide sustained and local release of small molecules and combination drugs. Herein, quantitative pharmacokinetic lessons from the clinic that can inform the next generation of materials development for local treatment of glioblastoma are summarized.